The impact of bank capital, bank liquidity and credit risk on profitability in postcrisis period: A comparative study of US and Asia - Faisal Abbas; Shahid Iqbal; Bilal Aziz (Cogent Economics & Finance, 2019)
The purpose of this study is to explore the influence of bank capital, bank liquidity level and credit risk on the profitability of commercial banks in the postcrisis period between 2011 and 2017 in Asian developed economies in comparison with the USA banking industry. The findings show that bank capital and credit risk influence profitability in Asian developed economies similar to in the USA commercial banks, whereas the impact of liquidity on the profitability of the USA large commercial banks is negative and positive on Asian developed economies commercial banks in the postcrisis era. The findings indicate that a 6% increase in capital leads to a 1% increase in profit, a 3.5% increase in liquidity leads to a 1% increase in profit. Specifically, larger banks generate 1% profit against a 1% increase in liquid assets. Medium size banks make 1% profit against a 3% increase in liquid assets, and small size banks produce 1% profit against a 7% increase in liquid assets. The findings show that liquidity influences profitability more intensively than capital, whereas the sign of coefficients is similar for large, small and medium-size banks. The results of this paper indicate that liquidity and bank capital have a positive impact on profitability, while credit risk has a negative influence on the profitability of banks. The findings of the simultaneous equations model indicate that bank capital has a positive impact on profitability in large and medium banks, whereas the profitability of banks influences the bank capital positively in case of large banks and negatively in case of medium banks.
Keywords: G21; G32; G33; 330; bank capital; bank liquidity; bank profitability; bank credit risk